Capacity-building for public health: http://peoples-uni.org - Richard F Heller; Virasakdi Chongsuvivatwong; Samson Hailegeorgios; John Dada; Perihan Torun; Rajan Madhok; John Sandars
The development of educational context around free and open-source materials available on the Internet has the ability to help build public health capacity in low- to middle-income countries. Inspiration to develop such a programme comes from the free and open-source software movement, where many hundreds of individuals have collaborated in the development of high-quality software freely available on the Internet, and its education counterpart of Open Educational Resource development. These reflect societal developments, especially those associated with Web 2.0. In a partnership across the global and digital divides, the People's Open Access Education Initiative (http://peoples-uni.org) has been established to embrace three aspects. First, identifying open-access materials linked to the competences required to tackle public health problems, with subsequent modifications to the materials by teachers and students to reflect local issues. Second, teaching through online facilitation by volunteers in conjunction with members of local universities. Third, accrediting learned competences. Situation analyses already performed suggest that the need for this education is great and that this solution may be feasible in many countries. Several partners have already agreed to be involved and exemplar course modules are being prepared. We call for volunteers to help take this initiative further.